Soluciones para la contaminación producida por las lámparas fluorescentes compactas. - Castillo Jaramillo, Paúl Hernan (2010)
The National Government considered necessary to optimize the consumption of electrical energy in the residential sector, therefore, through Ministry of Electricity and Renewable Energy undertook in the Project of substitution of six million incandescent lamp by Compact Fluorescent Lamps (LFCs) of twenty watts, with the intention of reduce approximately 200 megawatts of peak demand, in which the system requires large amount of generation. The LFC is an electronic device with a non-linear behavior, which is an emitter of electromagnetic disturbances that affect the waveform. The phenomenon that occurs is the fundamental wave distortion, caused by the presence of harmonics, which are waves having a frequency which is a multiple of them. The harmonic contamination can cause adverse effects on power systems, such as: possibility of amplification of some harmonics due to resonance, reduced performance of transport systems and electricity use, premature aging of the isolations from other electrical components that sharing the same network, measurement errors, etc. The research was conducted in marginal rural and urban sectors, which have higher incidence of lighting loads. This paper provides the individual degree of contamination of the economizer lamp and the contamination with other loads. It also proposes, some possible solutions to face this type of phenomena or considering alternatives involving to obtain similar energy saving with another type of lighting, but a lower degree of contamination.